Analyzing Information System Quality and Financial Information Quality: An Evidence of Local Government Organizations in Indonesia - Mohammad Anas; Rr Forijati; Mochamad Muchson (Qubahan Academic Journal)
End-user satisfaction is a potential substitute for utility in decision-making, user satisfaction is a measure of the extent to which an information system meets the information needs of its users. The purpose of this study was to determine the effect of the regional management information system quality and the financial information quality on end-user satisfaction. The method used in this research is descriptive and verification with a quantitative approach. The sample used in this study was 50 people in Local Government Organizations of Bandung City Government in Indonesia. The analytical tools used are Multiple Linear Regression, Correlation Analysis Test, Determination Analysis Test, and Partial Hypothesis Test. The results showed that the regional management information system quality had a positive and significant effect on the end-user satisfaction and the financial information quality had a positive and significant effect on end-user satisfaction at the Local Government Organizations of Bandung City Government. This study will contribute both to practitioners and academics related to end-user satisfaction in implementing the quality of information systems and the quality of financial information used. This study provides additional knowledge about financial information quality which is used as the basis for making decisions by local government organizations.